Group Theoretical Treatment of Substituted Saturated Fullerenes (C20H20-nXn) - Gupta, D. K.; Singh, S.; Sharma, L. N.; Agrawal, V. P. (Journal of Nepal Chemical Society, 2009)
An Investigation of the effects of various homosubstitutions on the symmetry group of saturated fullerene (C20H20-nXn) has been done. In substituted saturated fullerene (C20H20), tri and tetra substitutions in carbons within one hemisphere reduces the point group to Cs, whereas mono, di & penta substitutions at adjacent vertices within one hemisphere give C3v, C2v, and C5v, respectively. It has been found that di substitution in both hemispheres give the highest degree of symmetry.DOI: 10.3126/jncs.v23i0.2095J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page:43-44